(3JMHjQ GdJjSjQs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s; (3YKeGf Hf SYjO Hf YKeGf, CHh YeQh GdOGfj , GHf GdUjQaj,J (B444 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi JMHjQ GdJjSjQ hHYO adeG cGf cJGH GdJjSjQ ddEeGe CHh YeQh GdOGfi ef GUM cJH GdbQGAGJ , hChVM eG Cda Yf GdSHYI ef GdQhGjGJ s
(3BNQgG (B:s
(3hEf cGf BNQ GdShQI gGA cfGjI ehUhdI HhGh hMPa UdJgG ddSGcfjf aGYde HPdc ehabkG dWQb GdMb hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B177 - (3U(B266s
(3HgG fXGe GdJYbjHIs
(3cJHJ HQSe Gdabjg YHO Gddg Hf MSf GdCchYs
(3hGdRjGOI Ydi GdJjSjQ ecJhHI HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs